2021
DOI: 10.3390/polym13234222
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultra-High-Molecular-Weight Molecular Chains on the Morphology, Crystallization, and Mechanical Properties of Polypropylene

Abstract: The effects of the ultra-high-molecular-weight (UHMW) component of polypropylene (PP) on its rheological properties, crystallization behavior, and solid-state mechanical properties were investigated using various measurement techniques. The terminal relaxation time—determined by measuring the linear viscoelasticity—was increased by adding the UHMW component. The increase in the melt elasticity produced by adding the UHMW component was observed by measuring the steady-state shear flow, although the shear viscos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 51 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…A camera was set up on the other eyepiece to investigate the morphology. The details and some experimental results obtained by this machine were reported in our previous papers 36,37 . Figure 1 illustrates the experimental protocols for temperature and shear.…”
Section: Measurementsmentioning
confidence: 99%
“…A camera was set up on the other eyepiece to investigate the morphology. The details and some experimental results obtained by this machine were reported in our previous papers 36,37 . Figure 1 illustrates the experimental protocols for temperature and shear.…”
Section: Measurementsmentioning
confidence: 99%
“…This phenomenon, which is also observed in polyethylene, is attributed to the rise in tie-segments. Tie-segments refer to lengthy polymer chains that cross the amorphous regions as well as numerous crystalline domains. , A UHMWPE (∼5000 kg/mol) sample (Figure a) subjected to identical testing conditions endured a lower ultimate stress than 1656 kDa pDXL and lower ultimate strain than 1320 kDa pDXL. The mechanical performance of UHMW pDXL achieved here demonstrates the potential for pDXL as a chemically recyclable alternative to current thermoplastics (Figure a).…”
mentioning
confidence: 99%
“…The present result suggested that rubber-like deformation occurred during the reloading process. It was also demonstrated that stress/strain-induced crystallization barely occurred for PHBHHx at 25°C, which is quite different from the case for conventional crystalline polymers such as polyethylene and PP [48][49][50][51].…”
Section: Resultsmentioning
confidence: 99%